Estudo exploratório da secagem térmica de resíduo de cervejaria bagaço de malte - Garbin, Eudes Adan (2019)
The present work had as objective to carry out an exploratory study of the thermal drying and emptying of the solid residue of craft brewery – malt bagasse – with the intention of increasing its useful life cycle by removing moisture. Malt bagasse morphology was characterized with scanning electron microscopy (SEM) and elementally with dispersive energy spectroscopy (EDS). Different thermal drying techniques were carried out studied – heating chamber without air recirculation; wind tunnel, dredger with attached air blower – and dewatering with manual hydraulic press. The elemental composition of the malt bagasse showed higher concentrations for the elements silicon, carbon, oxygen, respectively, and the internal morphology with rounded aspects. It was possible to identify that the occurrence of silicon is associated with the husk of the malt bagasse. All data and results produced were tested statistically and showed non-parametric behavior. The results of the drying study for the different applied techniques were better for convection in relation to the heat chamber without air recirculation, when comparing the times to reach equilibrium moisture in all ranges of the tests. Still comparatively, the convection drying processes in the wind tunnel showed greater stability, higher values of average drying rate and shorter drying time – 255 minutes at 78.7°C. For the dredge tests, three distinct phases of temperature adjustment of the brewerr’s spent grains were characterized in relation to the temperature of the internal wall of the dredge. The first phase is of initial stabilization between these temperatures, the second is characterized by the temperature difference between them (wall temperature increases while the temperature of the brewer’s spent grains remains, indicating constant drying rate and moisture transfer – heat and mass) and the third final stabilization phase (when the temperature of the malt bagasse reaches and exceeds the temperature of the inner wall, indicating that the equilibrium moisture has been reached). The shortest drying time for the dredger was 180 minutes for operating conditions c3 and c4. In the press drain, 40% of the moisture was removed on a wet basis for an applied pressure of 1.0 t. It is concluded that the use of mechanical dewatering to remove moisture from the malt bagasse is promising and the thermal drying by convection proved to be more effective in relation to the drying by conduction for all the studied temperature ranges and, further, that the drying in dredge under conditions c3 and c4 it had the shortest drying time among all tests – 180 minutes.